Brothers and Sisters: Gender and the Labour Movement, a Feminist Labour Studies Conference at the Workers Arts and Heritage Centre, Hamilton, May 2002 - Iacovetta, Franca (Labour / Le Travail, 2003)
Reports on the various presentations made by academics and union activists at the day-long conference, including by Madelaine Parent.

Cleaning Up: Portuguese Women's Fight for Labour Rights in Toronto - Miranda, Susana P.; Iacovetta, Franca (Between the Lines, 2023)
This fascinating book uncovers the little-known, surprisingly radical history of the Portuguese immigrant women who worked as night-time office cleaners and daytime “cleaning ladies” in postwar Toronto. Drawing on union records, newspapers, and interviews, feminist labour historians Susana P. Miranda and Franca Iacovetta piece together the lives of immigrant women who bucked convention by reshaping domestic labour and by leading union drives, striking for workers’ rights, and taking on corporate capital in the heart of Toronto’s financial district. Despite being sidelined within the labour movement and subjected to harsh working conditions in the commercial cleaning industry, the women forged critical alliances with local activists to shape picket-line culture and make an indelible mark on their communities. Richly detailed and engagingly written, Cleaning Up is an archival treasure about an undersung piece of working-class history in urban North America. --Publisher's description

Sylvia Van Kirk: A Feminist Appreciation of Front-line Work in the Academy - Iacovetta, Franca (Finding a Way to the Heart: Feminist Writings on Aboriginal and Women's History in Canada, 2012)
“The 18 women and two men attending a course called History of Women in Canada” at the University of Toronto, wrote a Globe and Mail reporter in spring 1976,“could hardly wait to comment on their own experiences when instructor Sylvia Van Kirk introduced the subject of women’s rights in Canada.” The journalist, Constance Mungall, went on to describe the course—a new third-year seminar being offered by the (now defunct) interdisciplinary studies department at the University of Toronto—and the class (“After the vote: Did it make any difference?”) she had just observed. Sylvia had promoted discussion in the seminar by noting that “in the 1930s suffragette Nellie McClung had said the place of women in dating is ‘to wait… wait… wait’” and then asking if they thought it was still true today. Various students jumped in with their opinion and “the consensus was that it’s still the same and it’s hypocritical.” Mungall had attended the class as the course was nearing its end. By then, the seminar had covered a series of topics that would become standard fare for survey courses in Canadian women’s history, including Native women in the fur trade (a topic that, of course, Sylvia’s own research had helped make possible), white settler pioneers, and women in education, medicine, waged work, and moral and political reform movements. But these were also early days for women’s history and Sylvia was drawing on limited resources—still convincing people of the value of the field—and introducing little known historical female. --Introduction